Дети капитана Гранта. Двадцать тысяч лье под водой. - Верн Жюль (Полное издание в одном томе, 1993)
Экземпляры: Д. Б. (20230329) / Инвентарный номер: 49796 / Цена: 15.00 / Сис.шифр: 84 / Авт.знак: В 35 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-444